2016
DOI: 10.18203/2320-6012.ijrms20163769
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study on quality of life among acne vulgaris patients

Abstract: Background: In India, prevalence data from dermatology clinic in a teaching hospital in Varanasi reported acne in 50.6% of boys and 38.13% of girls in the age group 12-17 years. Though it is considered to be merely a cosmetic problem, it is associated with considerable psychological impairment which is comparable with certain chronic diseases. Acne patients are prone to low self-esteem, low self-confidence and social dysfunction which may lead to anxiety, depression, obsessive compulsiveness and sometimes suic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
5
4
0
Order By: Relevance
“…In the present study, 16-20 years was the most affected age group from acne vulgaris among males (60.31%) as well as females (47.06%) while the least affected age group was 31-35 years in males (0.76%) and 36-40 years in females (4.62%). Similar results were observed in the study by Pandey P et al [6] . Pandey P et al [6] revealed that majority (71% of participants) belonged to age group of 18 to 25 years with majority of students and 11.3% patients belonged to age group 26 to 35 years.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, 16-20 years was the most affected age group from acne vulgaris among males (60.31%) as well as females (47.06%) while the least affected age group was 31-35 years in males (0.76%) and 36-40 years in females (4.62%). Similar results were observed in the study by Pandey P et al [6] . Pandey P et al [6] revealed that majority (71% of participants) belonged to age group of 18 to 25 years with majority of students and 11.3% patients belonged to age group 26 to 35 years.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were observed in the study by Pandey P et al [6] . Pandey P et al [6] revealed that majority (71% of participants) belonged to age group of 18 to 25 years with majority of students and 11.3% patients belonged to age group 26 to 35 years. The relation between acne formation and BMI has been studied by many authors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These physiological changes that occur in the skin during puberty and adolescence have several effects, and this may also be a reason for seeking medical advice in many cases. 2 There were only a single comparative study by Radhamani et al on facial dermatoses in adolescent population. 3…”
Section: Discussionmentioning
confidence: 99%
“…9 Increased awareness and early intervention for the psychosocial and psychiatric sequel of acne can benefit patients. 10…”
Section: Introductionmentioning
confidence: 99%